Analysis of Halal Certification Process for Micro and Small Enterprises in Putussibau District - Istiqomah, Istiqomah; Deti, Sri; Susilawati, Susilawati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study is motivated by the low rate of halal certification ownership among Micro and Small Enterprises (MSEs) in Putussibau District, despite the government’s mandate requiring halal certification for all food and beverage products. Preliminary observations revealed that many business actors lack an understanding of the certification procedure, do not possess legal business documents such as NIB (Business Identification Number) and PIRT (Home Industry Food Production Certificate), and have not received guidance from Halal Product Process Assistants (P3H). These conditions indicate several barriers preventing MSEs from engaging in the halal certification process. This research aims to analyze: (1) the steps undertaken by MSEs in the halal certification process, (2) the obstacles encountered during the process, and (3) the underlying factors that prevent some business actors from applying for halal certification. A qualitative approach was used, with data collected through in-depth interviews, observation, and documentation involving 15 business actors with varying backgrounds and certification statuses. The findings show that MSEs that have undergone certification followed the self-declare scheme through the SiHalal application, completing steps such as registration, document submission, assistance by P3H, and verification. However, they still face technical difficulties, such as filling out digital forms, document revisions, and limited digital literacy. On the other hand, those who have not applied for certification often lack legal documentation, information, or perceive the certification as unnecessary or burdensome. The study recommends strengthening technical education, expanding mentorship, and simplifying the halal certification process to make it more accessible to MSEs in Putussibau District.